6 - Beyond Numbers: Unveiling the Subjective Well-Being of South Africa's Informal Sector Workers - Pretorius, Marinda; Ezli Durandt, (Africa Development, 2026)
The informal sector plays a modest but notable role in South Africa’s economy, but the living standards and financial circumstances of individuals in this sector often lead to prolonged entrapment. Despite these challenges, individuals employed in the informal sector exhibit average subjective well-being (SWB). Some studies have shown that the usual determinants of SWB have little impact on people employed in South Africa’s informal sector. This study aimed to confirm these findings by utilising a comprehensive dataset and concentrating on the informal sector as a whole. Employing an Ordered Probit model, we analysed the determinants of SWB in informal employment in South Africa using the merged Wave 5 (2017) dataset from the adult National Income Dynamics Study. The results revealed that only certain factors, including age, income, relative income, health status, and marital status, have a significant impact on SWB in the informal sector. Specifically, older age, lower health levels, above-average income, and experiences of divorce or separation are associated with a negative impact on SWB. Conversely, average income levels have a positive effect on SWB. We recommend targeted age-sensitive interventions, income enhancement programmes, as well as financial literacy and savings initiatives to help to improve the well-being of informal sector participants.